Long‐term cardiovascular outcomes of immune checkpoint inhibitor‐related myocarditis: A large single‐centre analysis - Lorenzo Braghieri; Ahmad Gharaibeh; Lubika Nkashama; Abdelrahman Abushouk; Osama Abushawer; Amir Mehdizadeh‐Shrifi; Bianca Honnekeri; Cassandra Calabrese; Venu Menon; Pauline Funchain; Patrick Collier; Diego Sadler; et al. (ESC Heart Failure)
Abstract Aims Immune checkpoint inhibitors (ICI) are the cornerstone of modern oncology; however, side effects such as ICI‐related myocarditis (irM) can be fatal. Recently, Bonaca proposed criteria for irM; however, it is unknown if they correlate well with cardiovascular (CV) ICI‐related adverse events. Additionally, whether incident irM portends worse long‐term CV outcomes remains unclear. We aimed to determine the incidence of long‐term CV comorbidities and CV mortality among irM patients. Patients and methods The ICI‐related adverse event (irAE) registry was queried to identify irM patients by using Bonaca criteria. Random controls were selected after excluding patients with other concomitant irAEs. Patients' demographics, comorbidities and myocarditis presenting features were gathered. Outcomes included 2‐year freedom from CV comorbidities (composite of atrial fibrillation, stroke, myocardial infarction and heart failure) and freedom from CV death. IrM was treated as a time‐varying covariate. Results Seventy‐six patients developed irM at a median of 167 days (mean age 69, 63.2% male, 47% lung cancer). Majority of patients had new wall motion abnormalities or EKG changes on presentation. Mean LVEF was 43%, median peak TnT was 0.81, and median NTproBNP was 2057 at irM onset. Two‐year freedom from CV comorbidities (67% vs 86.8%, P < 0.001) and death (93.4% vs 99.3%, P = 0.003) was lower among irM patients. Incident irM was an independent predictor of CV death (HR 8.28, P = 0.048), but not CV comorbidities (HR 2.21, P = 0.080). Conclusions This is the largest case–control study on irM highlighting worse long‐term CV outcomes. Future studies are needed to establish appropriate therapeutic strategies and efficient screening strategies for irM survivors.